2017
DOI: 10.1002/ece3.3597
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota composition is associated with environmental landscape in honey bees

Abstract: There is growing recognition that the gut microbial community regulates a wide variety of important functions in its animal hosts, including host health. However, the complex interactions between gut microbes and environment are still unclear. Honey bees are ecologically and economically important pollinators that host a core gut microbial community that is thought to be constant across populations. Here, we examined whether the composition of the gut microbial community of honey bees is affected by the enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 131 publications
(133 citation statements)
references
References 94 publications
5
116
1
Order By: Relevance
“…Notably similar bacterial communities have been found for workers from different populations and regions (Jeyaprakash et al 2003;Mohr and Tebbe 2006;Cox-Foster et al 2007;Martinson et al 2011;Moran et al 2012;Sabree et al 2012). However, in a recent study we demonstrated that some dominant members of the honey bee gut bacterial community differ in relative abundance when bees are exposed to different environmental landscapes (Jones et al 2017). Thus, there may also be differences in the gut community when bees are exposed to different local environments due to the different behavioural tasks they perform.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Notably similar bacterial communities have been found for workers from different populations and regions (Jeyaprakash et al 2003;Mohr and Tebbe 2006;Cox-Foster et al 2007;Martinson et al 2011;Moran et al 2012;Sabree et al 2012). However, in a recent study we demonstrated that some dominant members of the honey bee gut bacterial community differ in relative abundance when bees are exposed to different environmental landscapes (Jones et al 2017). Thus, there may also be differences in the gut community when bees are exposed to different local environments due to the different behavioural tasks they perform.…”
supporting
confidence: 80%
“…Interestingly in the context of the different behaviours performed by workers, B. apis has recently been shown to encode genes which may be involved in the degradation of secondary plant metabolites (Segers et al 2017), and this taxon has also been found to differ in abundance depending on the landscape type the worker honey bees are exposed to (Jones et al 2017). L. kunkeei on the other hand, a dominant crop (foregut) species rare in the gut, but also common in materials in the honey bee environment, was found to be higher in abundance in the gut communities of foraging workers than workers performing nursing tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut dissection and DNA extractions of individual guts was performed as outlined in Jones et al 2017. Illumina libraries were prepared following the method outlined by Caporaso et al 2012, by the Centre for Genomic Research, University of Liverpool.…”
Section: Methodsmentioning
confidence: 99%
“…Notably similar bacterial communities have been found for workers from different populations and regions (Jeyaprakash et al 2003; Mohr and Tebbe 2006; Cox-Foster et al 2007; Martinson et al 2011; Moran et al 2012; Sabree et al 2012). However, in a recent study we demonstrated that some dominant members of the honey bee gut bacterial community differ in relative abundance when bees are exposed to different environmental landscapes (Jones et al 2017). Thus, there may also be differences in the gut community when bees are exposed to different local environments due to the different behavioural tasks they perform.…”
Section: Introductionmentioning
confidence: 94%